Renal failure following insulin purging in atypical anorexia nervosa and type 1 diabetes mellitus - Rometsch, Caroline; Guthoff, Martina; Zipfel, Stephan; Stengel, Andreas (Frontiers in Psychiatry, 2023)
Objective: Anorexia nervosa (AN) and atypical anorexia nervosa (AAN) are severe and complex eating disorders that can be prevalent among individuals with type 1 diabetes mellitus (T1DM). Insulin purging, characterized by the intentional underuse / omission of insulin to control weight, is under-recognized in medicine and is a purging strategy of patients with AN or AAN and comorbid T1DM. Often, this can lead to renal failure, necessitating a (pancreas-) kidney transplantation. This article presents a comprehensive overview of the interplay between AN/AAN and T1DM and summarizes the evidence in literature.A narrative review is presented on basis of a detailed case study of a 32-year-old female with end-stage renal failure seeking (pancreas-) kidney transplantation displaying etiology, diagnosis, comorbidities, complications, and treatment of AN and AAN with emphasis on those patients with T1DM.Results: Insulin purging in patients with AN/AAN and coexisting T1DM can exacerbate T1DM complications, including accelerating the onset of end-stage renal failure. A multidisciplinary